Productive Remembering and Social Agency
XII, 264 p.
Keywords: Productive Remembering and Social Agency examines how memory can be understood, used and interpreted in forward-looking directions in education to support agency and social change. The edited collection features contributions from established and new scholars who take up the idea of productive remembering across diverse contexts, positioning the work at the cutting edge of research and practice. Contexts range across geographical locations (Canada, China, Rwanda, South Africa) and across critical social issues, from HIV & AIDS to the legacy of genocide and Indian residential schools, from issues of belonging, place, and media to interrogations of identity. This interdisciplinary collection is relevant not only to education itself but also to memory studies and related disciplines in the humanities and social sciences.